The plasma parameters and neutron yield at device of "Plasma focus" - A. M. Zhukeshov; Zh. M. Moldabekov; A. Ioffe (Physical Sciences and Technology, 2019)
Present work presents calculations and experimental studies on the formation and dynamics of plasma on the “plasma focus” set up. Physical conditions were determined and critical parameters were calculated for estimating the neutron yield for kilojoule and megajoule set ups. The results of plasma diagnostics and flow formation in the CPA-30 and PF-4 set ups are also shown. A comparison of calculated data and experimental values is performed. The value of the neutron yield parameter is justified and the possible cause of the appearance of saturation is indicated. The rationale for the development of further research in the direction of creating conditions for thermonuclear fusion in installations of the plasma focus type is given. The neutron flux was observed on high-voltage gas discharges with a specific geometry of the electrodes. The result of measuring the anisotropy of the neutron yield along the axial z and radial φ directions was equal to Yn(z)/Yn(φ)~ 2 ÷ 3, which contradicts the thermonuclear mechanism.